Pengaruh Berbagai Perlakuan Nutrisi Larutan Hidroponik Pada Pertumbuhan Tanaman Kangkung (Ipomoea aquatica) - Masriah Masriah (Bioscientiae, 2020)
Hydroponic cultivation systems are often applied to overcome the shortage of agricultural land in this case food crops, especially vegetables. Nutrient Film Technique (NFT) is the one of various ways to grow crops hydroponically. Hydroponic systems are carried out without the use of soil media and it can be an alternative solution for the efficient use of land. Uniformity of nutrients and nutrient solution concentration levels required to be adjusted. Nutrient solution as a water supply source and minerals. Nutrition is an important factor for the growth and quality of hydroponic plants should be appropriate in terms of the number of ion composition of nutrients. This study aimed to determined the effect of various treatments of hydroponic nutrient solution on plant growth kale. This study used a completely randomized design (CRD) with 4 treatments and 5 replications. Kale seed sowing in the growing media rockwool and nourished by nutrient A, nutrient B, combination of nutrients A and B (3: 1), or a combination of nutrients A and B (1: 3). Plant growth parameters such as plant height, number of leaves, wet weight, dry weight, and dry weight without root measured. Data were analyzed using analysis of variance ANOVA and DMRT test with Î± = 95%. The results showed that affect the nutrient solution hydroponic plant growth kale. Kale plants with a combination of nutrient A and nutrient B ratio of 3: 1 (treatment C) give the best response compared with other treatments.